(3GdeYde HahGFO eSdes - (3CHh YHO dGdg eMeO Hf Ydj Hf YeQ GdJejei GdeGRQis; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3hef cJGH GdJadjS bhdg Udi Gddg Ydjg hSde (B: (3ef GOQc eGdg HYjfg Yf QLd Ch EfSGf bO CadS hgh CMb Hg ef ZjQg s
(3BNQgG (B:s
(3JYde BNQ ShQI fRdJ ef dbQBf bdJ fYe ZPG LGA fUQ Gddg hGdaJM bGd UObJ hhbY ai fSNI GHf eGgGf ai CSfGO gPG GdMOjK ced GdSaQ GdKGfi ef GdeYde s
(3cJHJ HNW ajg HYV GdVHWs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs